REKONSTRUKSI TANGGUNG JAWAB ANCAMAN PIDANA MELALUI MEDIA ELEKTRONIK DI INDONESIA - SITTA SARAYA; YUSRINA HANDAYANI (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
The sophistication of technology and scientific development in Indonesia has influences all aspects of people's lives in Indonesia, such as imcreasing smartphone users day by day, electronic media or social media such as watshapp, instagram, twitter, telegram and facebook, which have a positive and negative impact in the other side.  The positive impact is that media helps to improve human activities in socializing and communicating with each other even if they do not meet face to face, as a form of self-actualization in daily interactions. Besides, the negative impact of scientific development of technology and information is the emergence of issues related to legal issues in Indonesia, some of criminal acts that happen cannot be prevented because of the misuse of technology and information through the media.  One of the biggest act that is very disturbing the society in daily life is threats through electronic media.The society complains or reports of threats throught electronic media has often difficult to be charged by law itself. Indonesia has actually have a specific legislation governing (Lex Specialis) regarding of Electronic Information and Technology, that is Undang-Undang Nomor 19 Tahun 2016 which is a  Amendments of Undang- Undang Nomor 11 Tahun 2008 concerning on Information and Electronic Technology as well.  The act of self-threat in the Criminal Law are regulated in general (Lex Genalis) in clausa 368 subsection (1) KUHP.This article will  discuss on the regulation of threats in Indonesia through electronic media, the reconstruction of criminal responsibility through electronic media in Indonesia based on justice, and the regulation of liability of threats through electronic media based on comparative studies from foreign countries.